Cracking potential and temperature sensitivity of metakaolin concrete. (1st September 2016) - Williams, Andrew; Markandeya, Ananya; Stetsko, Yuriy; Riding, Kyle; Zayed, A.
Research highlights: Metakaolin showed higher sensitivity to temperature and increased hydration heat. Metakaolin increased splitting tensile strength and restrained tensile stress. The use of metakaolin in concrete mixtures showed greater shrinkage and lower creep. B3 model was used to model early age creep. Conversion of Aft phases to Afm phases with metakaolin increased the amount of pores. Abstract: Metakaolin is a pozzolanic material with the potential to reduce permeability and chloride ingress; however, quantification of the effects of metakaolin use on the cracking sensitivity of concrete mixtures is needed to ensure that these improvements in performance are not compromised. This study was conducted to investigate the early age cracking potential due to restraint stresses from incorporating metakaolin in concrete. Calorimetry testing showed that metakaolin was more sensitive to temperature than mixtures with only Portland cement. Results showed more shrinkage, less stress relaxation, and higher restraint stress from the inclusion of metakaolin, potentially increasing cracking sensitivity of mixtures.